2012
DOI: 10.1088/0963-0252/21/1/015005
|View full text |Cite
|
Sign up to set email alerts
|

Plasma deposition in an ideal showerhead reactor: a two-dimensional analytical solution

Abstract: The interplay of gas flow and depletion by plasma dissociation determines the spatial distribution of species and the deposition uniformity in a plasma source. Many plasma reactors use a gas showerhead and the design of the flow dynamics is a critical aspect of the reactor performance. In this paper, plasma deposition is considered as chemically reacting gas flow in an ideal showerhead reactor. The gas fluid flow is described by finite-gap stagnation-point creeping flow. The distribution of neutral species acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
(69 reference statements)
1
15
0
Order By: Relevance
“…Howling et al used an SiH 4 /H 2 mixture to calculate the Peclet number (Pe = d ū/D, where d is the characteristic length, ū is the characteristic velocity, and D is the diffusion coefficient) in their CCP process conditions. Taking the binary diffusion coefficient for SiH 4 and H 2 at 100 Pa and 473 K to be 0.14 m 2 s −1 , the Pe was calculated as only 0.03 [8]. As our process conditions are similar to those of Howling et al, we confidently assumed that our gas transport phenomena are also observed under conditions of rapid diffusion.…”
Section: Effects Of the Heated Showerhead On Source Density Distribut...mentioning
confidence: 55%
See 1 more Smart Citation
“…Howling et al used an SiH 4 /H 2 mixture to calculate the Peclet number (Pe = d ū/D, where d is the characteristic length, ū is the characteristic velocity, and D is the diffusion coefficient) in their CCP process conditions. Taking the binary diffusion coefficient for SiH 4 and H 2 at 100 Pa and 473 K to be 0.14 m 2 s −1 , the Pe was calculated as only 0.03 [8]. As our process conditions are similar to those of Howling et al, we confidently assumed that our gas transport phenomena are also observed under conditions of rapid diffusion.…”
Section: Effects Of the Heated Showerhead On Source Density Distribut...mentioning
confidence: 55%
“…Therefore, chip manufacturers have continuously targeted high production efficiency [3][4][5]. Towards this objective, showerhead-type capacitively coupled plasma (CCP) PECVD reactors operated in the torr regime are often considered the best configuration for performing challenging processes [6][7][8]. This is because these reactors have the ability to deposit films with specified properties and with high uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…A significant problem in deposition reactors is the gas supply and the pumping of the plasma reactor [13]. This problem will be treated here in more detail.…”
Section: Problems Of Industrial Plasmasmentioning
confidence: 99%
“…From the perspective of the fluid pipe, to obtain a uniform fluid distribution without converting to turbulence in the chamber, the diffuser structure of the showerhead is more advantageous than the orifice structure. Therefore, the HC structure was tested experimentally and simulated for various trench structures [12,13]. In addition, simulations were performed on the repetitive form of the trenches, which can be applied to the showerhead structure.…”
Section: Introductionmentioning
confidence: 99%